Quite / Claudia Winkleman. - Winkleman, Claudia (HQ, 2020)
Claudia Winkleman's warmth, humour, no-holds-barred attitude, and smoky eyes have made her the favourite broadcaster of millions and a much-loved household name. She invites us all into her world. She shares her observations on topics such as the importance of melted cheese, why black coats are vital, how it's never okay to have sex with someone who has an opinion on your date outfit, how nurses are our most precious national treasure, and why colourful clothing is only for the under 10s. This is a love letter to life - the real, sometimes messy kind. 'Quite' celebrates friendship, the power of art, the highs and lows of parenting, and of course, how a good eyeliner can really save your life.